ENVIRONMENTAL POLICY AND CRITICAL INFRASTRUCTURE RESILIENCE: CHALLENGES OF SUSTAINABLE DEVELOPMENT DUE TO CLIMATE CHANGE - Marković, Jana; Stojanović, Lazar (Political Review, 2026)
According to scientific assessments by the Intergovernmental Panel on Climate Change, anthropogenic influence is the main driver of global warming, аs extreme weather events are becoming increasingly frequent and intense. Climate change and the negative consequences that these changes entail pose a serious threat to the sustainable development that the global community strives for. Due to the negative impact on the stability of ecosystems, the sustainability of economic development, and the security of human communities, the possibility of sustainable development goals being maintained in the long term is being questioned. Understanding sustainable development as an effort to ensure that current generations meet their needs without compromising the ability of future generations to do the same is becoming increasingly complex and challenging in the context of advancing climate change. Critical infrastructure that ensures the functioning of the state and society and ensures that the basic needs of the population are met is increasingly exposed to the effects of climate change, which is a particular problem given its importance. Extreme climate phenomena, land degradation, and environmental disasters are increasingly leading to serious social consequences, with critical infrastructure being extremely vulnerable. Disruptions in the supply of electricity, water, and food, the need to invest in repairing the damage caused, increased risks to the security of both the infrastructure itself and the wider environment, and reduced community resilience are just some of the consequences of endangering critical infrastructure. In light of climate challenges, investment in the protection and strengthening of the resilience of critical infrastructure must be an integral part of environmental policy, as a set of regulations and measures aimed at protecting and preserving the environment. The paper analyzes the correlation between environmental policy and the resilience of critical infrastructure from the perspective of climate change, starting from the theoretical foundations of environmental policy and the concept of resilience. Special emphasis is given to assessing the vulnerability of critical infrastructure in the context of climate-related natural disasters, as well as the interdependence of infrastructure systems that can lead to cascading effects and systemic disruptions. The paper examines the development of environmental policy, from its institutionalization to the contemporary global and European normative, strategic, and operational framework, including the 2030 Agenda, the Paris Agreement, the Sendai Framework, and relevant European Union policies. Through the analysis of examples of good practice from different countries, the paper highlights the importance of integrated and preventive measures in the planning, construction, and adaptation of infrastructure to climate risks. It concludes that strengthening the resilience of critical infrastructure is an effective instrument for reducing risks, ensuring the uninterrupted provision of essential services, and strengthening the security and stability of society, and that it must be systematically integrated into environmental policy and sustainable development strategies.